2001
DOI: 10.1182/blood.v98.7.2108
|View full text |Cite
|
Sign up to set email alerts
|

Differential homing and engraftment properties of hematopoietic progenitor cells from murine bone marrow, mobilized peripheral blood, and fetal liver

Abstract: The rate of reconstitution following hematopoietic stem cell (HSC) transplantation differs widely depending on the tissue source of the cells infused. To test the hypothesis that variability in engraftment kinetics is related to differences in the efficiency with which intravenously trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 34 publications
(20 reference statements)
4
69
2
Order By: Relevance
“…These studies nevertheless show that the property governing the superior homing of MPB HPC to marrow is independent of accompanying mature leukocytes or of certain host conditions and lies within a cell population which is enriched for HPC. Although several studies have shown [45] or implied [46][47][48] the potential for superior marrow homing of MPB HPC, opposing views, showing similar [49] or even inferior [10] homing of MPB, have also been reported. Reasons for the discrepancies are not clear but may include insufficient sample size [49] and immunophenotypic instead of functional definition of HPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies nevertheless show that the property governing the superior homing of MPB HPC to marrow is independent of accompanying mature leukocytes or of certain host conditions and lies within a cell population which is enriched for HPC. Although several studies have shown [45] or implied [46][47][48] the potential for superior marrow homing of MPB HPC, opposing views, showing similar [49] or even inferior [10] homing of MPB, have also been reported. Reasons for the discrepancies are not clear but may include insufficient sample size [49] and immunophenotypic instead of functional definition of HPC.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown [45] or implied [46][47][48] the potential for superior marrow homing of MPB HPC, opposing views, showing similar [49] or even inferior [10] homing of MPB, have also been reported. Reasons for the discrepancies are not clear but may include insufficient sample size [49] and immunophenotypic instead of functional definition of HPC. [10] Well-established functional in vivo assays were used to compare marrow homing of CFU-C present in ssBM or MPB.…”
Section: Discussionmentioning
confidence: 99%
“…Most available reports only outlined the differences in the kinetics and efficiency of engraftment, in homing properties and in cell cycle profiles between mobilized blood stem cells and those isolated from resting BM. [10][11][12][13] In view of the increased use of peripheral blood stem cells in clinical transplant settings, it is of relevance to investigate long-term functioning of stem cells isolated from different sources. In this study, we directly assessed the function of MPB stem cells compared to control BM stem cells when co-transplanted in a single recipient mouse in an in vivo competitive repopulation assay.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this, a ubiquitous expression of these integrins has been reported in less well-defined fetal HSPCs. 16,42,43 Integrin ␣6␤1 mediates FL LSK adhesion to lamininsIn in vitro adhesion assay (Figure 2), 10% to 15% of the isolated FL LSK cells adhered to recombinant laminin-411 and -511 isoforms and 25% adhered to placental laminin-511/521. Pretreatment of the cells with a protein kinase C activator, TPA, did not increase cell adhesion to the laminins (not shown).…”
mentioning
confidence: 99%